2022
DOI: 10.3233/jad-220256
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Panel of Plasma Proteins Predicts Progression in Prodromal Alzheimer’s Disease

Abstract: Background: A cheap and minimum-invasive method for early identification of Alzheimer’s disease (AD) pathogenesis is key to disease management and the success of emerging treatments targeting the prodromal phases of the disease. Objective: To develop a machine learning-based blood panel to predict the progression from mild cognitive impairment (MCI) to dementia due to AD within a four-year time-to-conversion horizon. Methods: We created over one billion models to predict the probability of conversion from MCI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…However, circulating levels of ApoB have been associated with risk for Alzheimer’s disease 62,63 and age-related cognitive decline 64,65 . Similarly, we observed that increased levels of circulating PCMT1, which has been shown to be neuroprotective in animal models of cognitive aging 66 , were causally associated with better cognitive task performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, circulating levels of ApoB have been associated with risk for Alzheimer’s disease 62,63 and age-related cognitive decline 64,65 . Similarly, we observed that increased levels of circulating PCMT1, which has been shown to be neuroprotective in animal models of cognitive aging 66 , were causally associated with better cognitive task performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the apolipoprotein B receptor (APOBR) was the strongest cis-pQTL signal associated with cognitive task performance in the present study, and has not been previously reported in comparable studies. However, circulating levels of ApoB have been associated with risk for Alzheimer’s disease 38,39 and age-related cognitive decline 40,41 . Similarly, we observed that increased levels of circulating PCMT1, which has been shown to be neuroprotective in animal models of cognitive aging 42 , were causally associated with better cognitive task performance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IGFBP-2 was found to mediate the relationship between RDW and mortality ( 42 ). IGFBP-2 has also been shown to be associated with early stages of Alzheimer’s disease progression ( 43 ). Our findings of adverse and beneficial trait associations with IGFBP-2 reflect the complicated nature of SASP and cellular senescence that can have different context-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…CSF and plasma IGFBP-2 levels are elevated in AD, and plasma levels of IGFBP-2 are associated with smaller hippocampal volumes and brain atrophy [55][56][57][58][59]. Moreover, high plasma levels of IGFBP2 have been shown to predict the risk of MCI conversion to dementia [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%